x + 12 - (3 - x) = -13 + x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
9/13 x 7/12 + 9/13 x 5/12 - 9/13
= 9/13 x (7/12 + 5/12 - 1)
= 9/13 x 0
= 0
4/13 x 5/12 + 4/13 x 7/12 - 4/3
= 4/13 x (5/12 + 7/12) - 4/3
= 4/13 x 1 - 4/3
= 4/13 - 4/3
= -40/39
![](https://rs.olm.vn/images/avt/0.png?1311)
1.\(13.87+13.12+13\)
\(=13\left(87+12+1\right)\)
\(=13.100=1300\)
2.Đề sai à ???
3.\(x\left(x+4\right)-x\left(x-6\right)\)
\(=x^2+4x-x^2+6x\)
\(=10x\)
\(=10.123=1230\)
1, \(13.87+13.12+13=13\left(87+12+1\right)=13.100=1300\)
2, bổ sung \(\left(x-3\right)2x+\left(x-3\right)y=\left(x-3\right)\left(2x+y\right)\)
Thay x = 13 ; y = 4 ta được : \(\left(13-3\right)\left(26+4\right)=10.30=300\)
3, \(x\left(x+4\right)-x\left(x-6\right)=x\left(x+4-x+6\right)=10x\)
Thay x = 123 ta được \(1230\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) = 35 . 18 - 35 . 18 = 0
2) = 45 - 5 . 12 + 5 . 9 = 45 - 60 + 45 = 30
3) = 24 . 16 - 24 . 5 - 16 . 24 - 16 . 5
= (24 . 16 - 16 . 24) - 5 (24 - 16)
= 0 - 5 . 8 = 0 - 40 = -40
4) = 29 . 19 - 29 . 13 - 19 . 29 - 19 . 13
= (29 . 19 - 29 . 19) - 13 (29 - 19)
= 0 - 13 . 10 = 0 - 130 = -130
5) = 31 . (-18) + 31 . (-81) - 31 . 1
= 31 [(-18) + (-81) - 1]
= 31 . (-100) = -3100
6) = (-12) . 47 + (-12) . 52 + (-12). 1
= (-12) . (47 + 52 + 1)
= (-12) . 100 = -1200
7) = 13 . 45 - 3 . 45
= 45 (13 - 3)
= 45 . 10 = 450
8) = (-48) + 48 . (-78) + 48 . (-21)
= (-48) . 1 + 48 . (-78) + 48 . (-21)
= 48 . (-1) + 48 . (-78) + 48 . (-21)
= 48 . [(-1) + (-78) + (-21)]
= 48 . (-100) = -4800
1) 35x18-5x7x18
= 35x18-35x18
= 35x(18-18)
= 35x0=0
3) 24.(16-5)-16.(24-5)
= 24.16-24.5-16.24-16.5
=[24.16-16.24]-[24.5-16.5]
= [ 24. (16-16)]- [(24-16).5]
= [24.0]-[8.5]
= 0-40=-40
4) 29.(19-13)-19.(29-13)
=29.19-29.13-19.29-19.13
=[ 29.19-19.29]-[ 29.13-19.13]
= [ 29.(19-19)]-[(29-19).13]
=[29.0]-[10.13]
= 0-130= -130
5) 31.(-18)+31.(-81)-31
= 31.(-18)+31.(-81)-31.1
= 31.[(-18)+(-81)-1]
=31.(-100)
= -3100
6);7);8 tương tự 4);5);6)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) = \(\frac{3}{5}\)
2) =\(\frac{6}{7}\)
3)\(\frac{9}{13}\)
4)\(\frac{4}{13}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
đề rối
\(x+\frac{3}{10}+x+\frac{3}{11}+x+\frac{3}{12}=x+\frac{3}{13}+x+\frac{3}{14}\)
\(\Leftrightarrow3x+\left(\frac{3}{10}+\frac{3}{11}+\frac{3}{12}\right)=2x+\left(\frac{3}{13}+\frac{3}{14}\right)\)
\(\Leftrightarrow3x+\frac{181}{220}=2x+\frac{81}{182}\)
\(\Leftrightarrow3x-2x=-\frac{181}{220}+\frac{81}{182}\)
\(\Leftrightarrow x=-\frac{181}{220}+\frac{81}{182}=\frac{-7561}{20020}\)
hay là
\(\frac{x+3}{10}+\frac{x+3}{11}+\frac{x+3}{12}=\frac{x+3}{13}+\frac{x+3}{14}\)
\(\Leftrightarrow\frac{x+3}{10}+\frac{x+3}{11}+\frac{x+3}{12}-\frac{x+3}{13}+\frac{x+3}{14}=0\)
\(\Leftrightarrow\left(x+3\right)\left(\frac{1}{10}+\frac{1}{11}+\frac{1}{12}-\frac{1}{13}+\frac{1}{14}\right)=0\)
\(\Leftrightarrow x+3=0\)( vì \(\left(\frac{1}{10}+\frac{1}{11}+\frac{1}{12}-\frac{1}{13}+\frac{1}{14}\right)\ne0\))
\(\Rightarrow x=-3\)
`x + 12 - (3 - x) = -13 + x`
`x + 12 - 3 + x = -13 + x`
`2x +9 = -13 + x`
` 2x - x = -13 - 9`
`x = -22`
x+12-(3-x)=-13+x
x+12-3+x=-13+x
2x+12-3=-13+x
2x+9=-13+x
2x+9-x=-13
x+9=-13
x=-13-9
x=-22